Physics Application in Traditional Archery: Sight-lines Method for Aiming Using a Traditional Bow - Ibnu Jihad (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
The absence of bow sight in a traditional bow can be replaced by introducing sight lines as a reference for accurate elevation angles in archery. Assuming a quadratic drag force acting on the arrow, a sight line can be calculated by using the values of target distances, initial arrow speed, arrow velocity decay, and the stance of the archer. This method can improve shooting accuracy for various target distances.